Protesto indígena na Colômbia: a Minga em questão - Elizabeth del Socorro Ruano (Ciências Sociais Unisinos)
The study of the Minga, a protest that took place in October and November of 2008 in Colombia, intends to explore the category of “protest” by showing the specificities of contemporary relations between the national State and the indigenous people. The analysis dialogues with scholars who have highlighted the political character of the social protest. Document analysis, participant observation, and interviews were the instruments used to gather information, which demonstrates that the protests become a political act through strategies that publicly constrain government officials. This situation leads to crises of legitimacy that can be politically capitalized by protesters. However, in the interministerial meetings, where the dialogue between the protesters and the state representatives takes place, the governmental strategies designed to delay and neutralize the protests prevail.